A preliminary radiological study emphasizing on anatomic patterns of pterygoid plates using cone beam computed tomography - S Annapoorani; A Winnifred Christy; T Jones Rajadeva Thambi; R Mahalakshmi (Wolters Kluwer Medknow Publications, 2023)
Introduction: This article emphasizes the importance of pterygoid plates (PP) and their anatomical characteristics while adding points about the relation between PP asymmetry and resulting temporomandibular joint disorders (TMJD). Materials and Methods: This retrospective study analyzes 100 Cone Beam Computed Tomography images. Morphometric analysis of the shape, thickness, and angulation of PP and pterygoid fossae (PF) was done. Statistical analysis was performed using Paired t-test and ANOVA. Results: Five different shapes of PP were noted, the tapered form was more prevalent (P < 0.01), and the needle form had the least thickness, which is prone to fracture. Three different shapes of PF were noted, namely U, V, W. V shape was more common. Males had increased thickness than females in medial and lateral pterygoid (P = 0.005). Conclusion: Owing to their location and relations to their adjacent structures, PP plays a vital role during various surgical procedures. Oral and maxillofacial surgical procedure planning must be done following the evaluation of PP as there is an increased risk of complication due to PP fracture. PP gives attachment to a few muscles and ligaments essential for jaw movements. Any deviation of PP from normal may result in temporomandibular joint disorders.